Stress-Related Molecular Biomarkers to Monitor the Effects of Global Changes on Calcifying Reef-Forming Organisms: A Review in the Mediterranean - Verdiana Vellani; Matteo Oliva; Carlo Pretti; Monia Renzi (Journal of Marine Science and Engineering)
Molecular biomarkers are valuable tools universally used for early warning monitoring due to their ability to detect stress at subcellular scales, even before visible or lethal changes occur in organisms. Their use is considered a priority, especially for those organisms that will be most affected by the global changes underway, such as sessile benthic organisms in shallow waters. Among them, reef-forming species play a vital role in maintaining biodiversity in temperate aquatic ecosystems. Little information is available on these organisms in the Mediterranean on the use of health status indicators at the level of biochemical responses. This review aims to highlight the need for a more in-depth analysis of the conditions of bioconstructors in a climate change scenario by using stress biomarkers. To achieve this goal, about 140 articles were selected based on a keyword search for a graphical visualization of the state of the art of the literature. Based on this overview, a literature review of selected works in the Mediterranean area was conducted to select both model organisms and molecular biomarkers for future analyses in this field. From the literature review, a gap analysis was produced, focusing on the main stressors related to global change and their effects on bioconstructors. Furthermore, an attempt was made to quantify and clarify the use of the various molecular biomarkers in different contexts. These findings should be considered in an updated protocol for monitoring programs and efforts at the European level, as outlined by the Marine Strategy Framework Directive (MSFD 2008/56/EC).